Prevalence of falciparum malaria parasitaemia and risk factors associated among residents of a peri urban community in Akure, Nigeria - Oluwaseun Bunmi Awosolu, Zary Shariman Yahaya, Kehinde Oluwatobi Elegbede (International Journal of Advanced Science and Technology, 2020)
Malaria is a serious global public health challenge caused by parasite belonging the genus Plasmodiumand it is known to have hindered growth and development in Nigeria and worldwide. An investigation onthe prevalence and risk factors enhancing local transmission of Plasmodium falciparum was carried out inIpinsa, Akure South Local Government Area (LGA) of Ondo State, Nigeria. Volunteered individuals whichtotaled three hundred (300) were examined for the parasite using thick and thin blood smears viewed underthe x100 objective lens of the light microscope. The demographic and socio-economic characteristics ofthe study population were determined through administration of questionnaires to the participants. Overallprevalence of 78.3% was recorded among the participants. Males had a higher rate of infection (80.3%)than females (76.7%) though no significant difference was found (P<0.05). Individuals within the age groupof 21 and above had the highest infection prevalence of 95.7% which was significant (P<0.05) comparedto individuals within the age group 11 to 16 who had the least rate of infection (57.5%). With respect tosex, the highest parasite density was observed in females (2068 parasites/µl) while the least was observedin males (1806 parasites/µl). The results also showed that with respect to age, the highest parasite densitywas spotted among 5 years and below (2206 parasites/µl) while the least parasite density was observedamong 21 years and above (1680 parasites/µl). The subject’s income per month also played a significant(P<0.05) role as a determining factor for malaria infection. The highest malaria infection prevalence of85.2% was recorded among individuals who earn ≤18000 Naira income/month while the least malariainfection (56.9%) was recorded among those who earn ≥31000 Naira income/month. In view of the outcomeof current study, it is apparent that malaria is endemic in Ipinsa and control interventions should bedeployed.